Community satisfaction levels on the housing reconstruction project after Mentawai tsunami in 2010 - a case study at Sipora Island. Issue 1 (September 2020) - Ophiyandri, T; Hidayat, B; Ghiffari, C
Abstract: An earthquake accompanied by tsunami that occurred in the Mentawai Islands on 25 October 2010 brought many casualties and damage on housing. As a result, people living on the coastline lost their homes and has to be relocated to safer places. The implementation of the housing reconstruction program was based on the relocation approach. Unsafe coastal locations require the communities to move to higher ground which unfortunately at the forest areas of Mentawai. The success of the reconstruction of the housing sector can be an indicator of success in the implementation of post-disaster reconstruction. The purpose of this research is to identify the community satisfaction levels on the housing reconstruction projects in Sipora island. This research was conducted in South Sipora by conducting structured interview on 20 respondents spread across four villages. Respondents were invited to rate the satisfaction levels from very dissatisfied until very satisfied with points values 1-5. The results show that the level of community satisfaction was 2.91. The main problem was caused by a long delay in the start of the reconstruction program. In addition, there are still problems after the house is completed, such as the lack of availability of clean water and public facilities.